Inhomogeneous torsional creep problems in anisotropic Orlicz Sobolev spaces - Mihailescu, Mihai (2018)
In this paper, we study the asymptotic behavior of the sequence of solutions for a family of torsional creep-type problems, involving inhomogeneous and anisotropic differential operators, on a bounded domain, subject to the homogenous Dirichlet boundary condition. We find out that the sequence of solutions converges uniformly on the domain to a certain distance function defined in accordance with the anisotropy of the problem. In addition, we identify the limit problem via viscosity solution theory.